E-Learning is Effectively Used for Management for IT Service Courses - Ambiyar, Ambiyar; Rizal, Fahmi; Suhaedin, Enjang; Maulana, Ilham Tri (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This development research ailems to develop learning media (E-Learning) for employee class in management for IT service courses at Metamedia University. E-Learning is designed to improve student learning outcomes, so students can fully understand the material provided. This study uses the Instructional Development Institute development method. IDI procedures are defining, developing, and evaluating. The type of data is primary data where the data obtained from media experts, lecturers and students. Data were analysed using Descriptive Data Analysis Techniques which describe the validity, practicality, and effectiveness of using E-Learning. The results obtained from this research and development are as follows; (1) The validity of E-Learning is stated to be very valid in terms of content and interest with a total validity value of 84%, while the design aspect is stated to be valid with a total value of 85% (2) The practicality of E-Learning is based on the lecturer's response after through validation is stated to be practical with a total score of 87.5%, while the practicality of E-learning based on student responses after going through validation is stated to be practical with a total score of 80% (3) The results obtained from this study are E-Learning is effectively used by employee class students with a graduation rate of 48 student or 89% of 54 students. Based on the findings of this study, it was concluded that E-Learning is valid, practical and effective for use as a learning medium.